THE IMPACT OF CIGARETTE SMOKING ON SEMEN QUALITY AND MALE FERTILITY: A SYSTEMATIC REVIEW - Kotlarska, Klaudia Magdalena; Kotlarski, Wojciech; Mainka, Tomasz Stanisław; Sergejuk, Emil (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Introduction: Male infertility is an important public health issue, and lifestyle factors are increasingly recognized as key determinants of reproductive health. Cigarette smoking may negatively affect semen quality through oxidative stress, DNA damage, and hormonal disturbances, although findings remain inconsistent. This systematic review aimed to assess the association between cigarette smoking and semen quality in men.Methods: Data were selected using the PRISMA flow diagram. PubMed and EMBASE were searched for studies published between 2005 and 2025 using the keywords smoking, cigarette smoking, semen quality, sperm concentration, sperm motility, sperm morphology, and male infertility. After screening according to predefined criteria, 29 studies were included. The selected studies examined the association between cigarette smoking and semen quality parameters, including sperm concentration, motility, morphology, and semen volume, in relation to male infertility.Results: Seventeen studies were included in the qualitative synthesis. Cigarette smoking was associated with poorer semen quality, particularly lower sperm concentration, total sperm count, motility, and abnormal morphology. Smoking was also linked to oxidative stress, sperm DNA fragmentation, altered chromatin remodeling, membrane dysfunction, hormonal changes, and epigenetic abnormalities. Several studies suggested a dose-dependent effect, while smoking cessation was associated with improvement in selected semen parameters, especially semen volume, sperm concentration, and total sperm count.Conclusion: Cigarette smoking appears to be an important modifiable risk factor for impaired semen quality and reduced male fertility. Its harmful effects involve both conventional semen abnormalities and deeper molecular sperm damage. Smoking cessation may partially reverse these changes, supporting its role in male infertility prevention and management.